2019
DOI: 10.3389/fimmu.2019.01542
|View full text |Cite
|
Sign up to set email alerts
|

Invariant NKT Cells From Donor Lymphocyte Infusions (DLI-iNKTs) Promote ex vivo Lysis of Leukemic Blasts in a CD1d-Dependent Manner

Abstract: Allogeneic hematopoietic cell transplantation (allo-HCT) is a curative treatment option for hematologic malignancies but relapse remains the most common cause of death. Infusion of donor lymphocytes (DLIs) can induce remission and prolong survival by exerting graft-vs.-leukemia (GVL) effects. However, sufficient tumor control cannot be established in all patients and occurrence of graft-vs.-host disease (GVHD) prevents further dose escalation. Previous data indicate that invariant natural killer T (iNKT) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The evidence is somewhat thinner in the context of hematologic malignancies, however, CD1d has been shown to be expressed on multiple myeloma cells ( 159 , 160 ), as well as AML cells ( 161 ) and iNKT exhibited reactivity to CD1d positive tumor cells in vitro in a α-GalCer–dependent manner. In line with these findings, iNKT cells from donor lymphocyte infusion (DLI) could be expanded ex vivo and were capable of lysing leukemia cell lines and patient AML cells in CD1d-dependent manner ( 162 ).…”
Section: Inkt Cellsmentioning
confidence: 83%
“…The evidence is somewhat thinner in the context of hematologic malignancies, however, CD1d has been shown to be expressed on multiple myeloma cells ( 159 , 160 ), as well as AML cells ( 161 ) and iNKT exhibited reactivity to CD1d positive tumor cells in vitro in a α-GalCer–dependent manner. In line with these findings, iNKT cells from donor lymphocyte infusion (DLI) could be expanded ex vivo and were capable of lysing leukemia cell lines and patient AML cells in CD1d-dependent manner ( 162 ).…”
Section: Inkt Cellsmentioning
confidence: 83%
“…In this regard it is important that we have previously found that eicosanoid-producing interactions between human iNKT cells and monocyte-derived DCs actually led to enhanced neutrophil-mediated control of cutaneously administered Candida albicans ( Xu et al, 2016 ). Moreover, increased iNKT cell frequency after human haplo-identical hematopoietic transplantation is associated with lower cancer relapse rates ( de Lalla et al, 2011 ; Casorati et al, 2012 ), and human iNKT cells expanded from blood or donor lymphocyte infusions have been shown to directly lyse primary human leukemic blasts in vitro ( Schmid et al, 2018 ; Jahnke et al, 2019 ). Thus, there is reason for optimism that iNKT cell immunotherapy may actually promote key aspects of immune function after hematopoietic transplantation, while also limiting the inflammatory activation of cord T cells and promoting HSPC engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that patients with hematologic malignancies who maintained remission after hHSCT had full reconstitution of iNKT cells, whereas patients who relapsed did not. 126 IFN-γ production 126 or direct killing of AML blasts in a CD1d-dependent manner 129 may explain the role of iNKT cells in maintaining antitumor immunity after allo-HSCT.…”
Section: Immune Evasion/suppression In Amlmentioning
confidence: 99%